Understanding the intracellular trafficking and intercellular transport of potexviruses in their host plants - Park, Mi-Ri; Jeong, Rae-Dong; Kim, Kook-Hyung (Frontiers in Plant Science, 2014)
The movement of potexviruses through the cytoplasm to plasmodesmata (PD) and through PD to adjacent cells depends on the viral and host cellular proteins. Potexviruses encode three movement proteins (referred to as the triple gene block or TGB1–3). TGB1 protein moves cell-to-cell through PD and requires TGB2 and TGB3, which are endoplasmic reticulum (ER)-located proteins. TGB3 protein directs the movement of the ER-derived vesicles induced by TGB2 protein from the perinuclear ER to the cortical ER. TGB2 protein physically interacts with TGB3 protein in a membrane-associated form and also interacts with either CP or TGB1 protein at the ER network. Recent studies indicate that potexvirus movement involves the interaction between TGB proteins and CP with host proteins including membrane rafts. A group of host cellular membrane raft proteins, remorins (REMs), can serve as a counteracting membrane platform for viral RNP docking and can thereby inhibit viral movement. The CP, which is a component of the RNP movement complex, is also critical for viral cell-to-cell movement through the PD. Interactions between TGB1 protein and/or the CP subunit with the 5'-terminus of genomic RNA (vRNA) form RNP movement complexes and direct the movement of viral RNAs through the PD. Recent studies show that tobacco proteins such as NbMPB2C or NbDnaJ-like proteins interact with the stem-loop 1 RNA located at the 5'-terminus of PVX vRNA and regulate intracellular as well as intercellular movement. Although several host proteins that interact with vRNAs or viral proteins and that are crucial for vRNA transport have been screened and characterized, additional host proteins and details of viral movement remain to be characterized. In this review, we describe recent progress in understanding potexvirus movement within and between cells and how such movement is affected by interactions between viral RNA/proteins and host proteins.